Integrating information literacy into the economics classroom: a faculty-librarian collaboration. (2016) - Kim, Gil; Kubo, Hiromi
Information literacy is "an intellectual framework for understanding, finding, evaluating, and using information-activities which may be accomplished in part by fluency with information technology, in part by sound investigative methods, but most importantly, through critical discernment and reasoning" (ACRL, 2000). In the current environment of information abundance driven by ever-evolving information and communication technology, information literacy is even more vital for students in higher education. However, literature on economic education shows that developing and assessing information literacy skills has not been fully incorporated into economics curricula. This study seeks to address this issue by embedding information literacy instruction into an economics general education course, assessing student learning outcomes, and analysing how information literacy instruction supports the learning process in an economics course. At California State University, Fresno, collaboration between an economics faculty member and a librarian liaison to the economics department resulted in information literacy instruction being incorporated into one of the two sections of the principles of macroeconomics course, from the fall 2013 semester to the spring 2015 semester. The results of the pre- and post-test assessment showed that the information literacy instruction integrated into the ECON 50 coursework helped develop students' information research skills and understanding of information literacy concepts.